An autonomous navigation system integrated with air data and bionic polarization information. (September 2019) - Guo, Xiaoyu; Yang, Jian; Du, Tao; Liu, Wanquan
One of the most significant challenges for an unmanned aerial vehicle (UAV) is to autonomously navigate in complex environments, as the signals from the global positioning system (GPS) are subject to disturbance and interference. To improve the autonomy and availability of the UAV navigation system without GPS, we design a new autonomous navigation system and implement it for real applications in this paper, in which one integrates the inertial measurement unit (IMU), the bionic polarization sensor (BPS), and the air data system (ADS). The BPS can provide effective heading angle measurement, and the ADS is used to output information for continuous velocity and height. The combination of BPS and ADS is a solution the inertial error drift. Kalman filter is selected to estimate the error state of the integrated navigation system based on the measurements from the BPS and ADS, and then the estimation is used to correct the navigation system error in real time. The simulation and experimental results have shown that the new integrated navigation system can perform with high precision and autonomy without GPS signal.